The role and problems of managerial accounting organization on the enterprises - Bykovska, A. (ТДАТУ, 2018)
EN: The specifics of the managerial accounting organization at the enterprise are considered. The main systems of managerial accounting organization in Ukraine are analyzed. Their advantages and disadvantages are highlighted. The efficiency of the application of the world experience along with the national practice of management is substantiated. It is determined how close the relationship between the theoretical approaches of accounting with practical application is. UK: Було розглянуто особливості організації управлінського обліку на підприємстві. Проаналізовано основні системи організації управлінського обліку в Україні, виокремлено їх переваги та недоліки. Обґрунтовано ефективність впровадження світового досвіду поряд з вітчизняною практикою управління. Визначено, наскільки тісним є взаємозв ’язок теоретичного підходу ведення внутрішньогосподарського обліку з практичним застосуванням.
Keywords: accounting with practical application is; accounting organization at the enterprise; організація управлінського обліку на підприємстві; практика управління